IMPLEMENTASI PEMBELAJARAN MENGGUNAKAN MEDIA GOOGLE CLASSROOM DAN WHATSAPP UNTUK MENINGKATKAN HASIL BELAJAR SISWA PADA SMAN 1 WOLOWAE - MOSES RIKU (Pusat Pengembangan Pendidikan dan Penelitian indonesia (P4I), 2022)
To improve student learning outcomes in Chemistry subjects at SMA Negeri 1 Wolowae for the 2020/2021 academic year, research was conducted to identify online learning using Google Classroom and WhatsApp media. The research was conducted using the Classroom Action Research method which was carried out in two cycles. Each cycle consists of four stages, namely planning, implementation, observation and reflection. The research subjects were students of class X IPA SMA Negeri 1 Wolowae in the academic year 2020/2021 as many as 24 people consisting of 6 boys and 18 girls. The test results obtained in online learning using Google Classroom and WhatsApp media are the data collection techniques in this study. Based on the results of the study, it was found that online learning using Google Classroom and WhatsApp media in class X IPA students of SMA Negeri 1 Wolowae in the 2020/2021 academic year on Atomic Theory material experienced an increase. The results showed that student learning outcomes in online learning using Google Classroom and WhatsApp media increased from 70.83% in the first cycle to 87.50% in the second cycle. This shows that the learning outcomes of class X science students at SMA Negeri 1 Wolowae for the academic year 2020/2021 in Chemistry subjects with Atomic Theory material increased by 16.67%. Based on the results of the study, it can be concluded that online learning using Google Classroom and WhatsApp media can improve chemistry learning outcomes in class X science students at SMA Negeri 1 Wolowae in the 2020/2021 academic year. Online learning using Google Classroom and WhatsApp media can be a solution and alternative in implementing the learning process during the Covid-19 pandemic. ABSTRAKUntuk meningkatkan hasil belajar siswa pada Mata pelajaran Kimia di SMA Negeri 1 Wolowae Tahun Pelajaran 2020/2021 maka dilakukan penelitian guna mengidentifikasi pembelajaran daring menggunakan media Google Classroom dan WhatsApp. Penelitian dilakukan menggunakan metode Penelitian Tindakan Kelas yang dilaksanakan dalam dua siklus. Setiap siklus terdiri dari empat tahapan yakni perencanaan, pelaksanaan, pengamatan dan refleksi. Subjek penelitian adalah siswa kelas X IPA SMA Negeri 1 Wolowae Tahun Pelajaran 2020/2021 sebanyak 24 orang terdiri dari 6 orang laki- laki dan 18 orang perempuan. Hasil tes yang diperoleh pada pembelajaran daring menggunakan media Google Classroom dan WhatsApp merupakan teknik pengumpulan data dalam penelitian ini. Berdasarkan hasil penelitian diperoleh bahwa pembelajaran daring menggunakan media Google Classroom dan WhatsApp pada siswa kelas X IPA SMA Negeri 1 Wolowae Tahun Pelajaran 2020/2021 pada materi Teori Atom mengalami peningkatan. Hasil penelitian menunjukkan bahwa hasil belajar siswa pada pembelajaran daring menggunakan media Google Classroom dan WhatsApp terjadi peningkatan dari 70,83% pada siklus pertama menjadi 87,50% pada siklus kedua. Hal ini menunjukkan bahwa hasil belajar siswa kelas X IPA SMA Negeri 1 Wolowae tahun pelajaran 2020/2021 pada mata pelajaran Kimia dengan materi Teori Atom meningkat sebesar 16,67%. Berdasarkan hasil penelitian maka dapat disimpulkan bahwa pembelajaran daring menggunakan media Google Classroom dan WhatsApp dapat meningkatkan hasil belajar Kimia pada siswa kelas X IPA SMA Negeri 1 Wolowae Tahun Pelajaran 2020/2021. Pembelajaran daring menggunakan media Google Classroom dan WhatsApp dapat menjadi solusi dan aternatif dalam pelaksanaan proses pembelajaran selama masa pandemi Covid-19.